Landmark-Based Geometric Morphometric of Apis dorsata and A. d. binghami Wing Venation in Indonesian Archipelagos - Innayah Zahara; Fahri Fahri; Jacobus S.A Lamerkabel; Qashiratuttarafi Qashiratuttarafi; Berry Juliandi; Rika Raffiudin (Bogor Agricultural University, Indonesia, 2022)
The giant honey bee Apis dorsata has a vast distribution in Asia, including in the Indonesian archipelagos, whereas A. d. binghami is endemic to Sulawesi Island. This research aimed to analyze the variations of landmarks in wing venation of A. dorsata from Sumatra, Belitung, Java, Sumbawa, Moluccas islands, and A. d. binghami in Sulawesi, based on geometric morphometric analysis. Nineteen landmarks from 200 wing venations were analyzed using Thin Plate Spline software. Our study found landmarks 16 and 17, known as Cubital Index in traditional morphometrics, contributed to the wing shape of A. dorsata and A. d. binghami Among all samples, these two landmarks show high displacement in the wing shape of A. d. binghami in Sulawesi and A. dorsata in the Moluccas. On the contrary, we found that the Sumatra, Belitung, and Java Apis dorsata revealed low displacement in the deformation grid; resulting in their shapes being more similar to the reference landmark. The variations of wing shape separate A. d. binghami from Sulawesi and Sumbawa in the Principle Component Analysis and agreement with the Neighbor-joining tree. Therefore, the geometric morphometric based on landmarks of wing venation is a powerful tool to discriminate the subspecies level of A. dorsata.